Growth differentiation factor-15 — a new indicator of unfavorable prognosis in uncomplicated myocardial infarction - A. S. Sabirzyanova; A. S. Galyavich; L. V. Baleeva; Z. V. Galeeva (Российский кардиологический журнал, 2023)
Aim. To evaluate the role of growth differentiation factor-15 (GDF-15) in long-term prognosis in patients with uncomplicated myocardial infarction (MI).Material and methods. The study included 118 patients with uncomplicated ST-elevation and non-ST-elevation MI. In addition to the routine examination, all patients were analyzed for GDF-15, as well as the N-terminal pro-brain natriuretic peptide (NT-proBNP) by enzyme immunoassay in the first 48 hours from the onset of MI symptoms. The changes in the patients' condition were assessed by questioning after 1, 3, 6, 12 months, as well as the analysis of medical records in the event of repeated cardiovascular events and deaths. The endpoints were cardiovascular death, hospitalization for recurrent MI, and/or unstable angina. To assess the value of quantitative variables in predicting recurrent cardiovascular events, the ROC analysis was used. The survival function of patients was assessed using the Kaplan-Meier method.Results. Twelve-month follow-up revealed 29 recurrent cardiovascular events, including 2 deaths and 8 recurrent MIs. GDF-15 was predictive of recurrent cardiovascular events with a sensitivity of 77,3% and a specificity of 56,2% (ROCAUC, 0,7±0,065 (95% confidence interval (CI), 0,572-0,827), p=0,004). Patients with GDF-15 ≥2,075 ng/mL had a higher risk of recurrent cardiovascular events (hazard ratio (HR), 3,4 (95% CI, 1,342-8,613), p=0,005). Another prognostic factor influencing the rate of recurrent cardiovascular events was NT-proBNP. An NTproBNP level ≥578 pg/mL was associated with an increased risk of cardiovascular death and rehospitalization for unstable angina and recurrent MI (HR, 4,3 (95% CI 1,828-10,239), p=0,00019).Conclusion. The combined increase in GDF-15 ≥2,075 ng/mL and NT-proBNP ≥578 pg/mL in patients with uncomplicated MI increases the risk of recurrent cardiovascular events over the next 12 months (HR, 4,5 (95% CI, 2,087-9,736), p=0,00018).